Direct Observation of Oxygen Rebound with an Iron-Hydroxide Complex - Zaragoza, Jan Paulo T. (J Am Chem Soc, 2017)
The rebound mechanism for alkane hydroxylation was invoked over 40 years ago to help explain reactivity patterns in cytochrome P450, and subsequently has been used to provide insight into a range of biological and synthetic systems. Efforts to model the rebound reaction in a synthetic system have been unsuccessful, in part because of the challenge in preparing a suitable metal-hydroxide complex at the correct oxidation level. Herein we report the synthesis of such a complex. The reaction of this species with a series of substituted radicals allows for the direct interrogation of the rebound process, providing insight into this uniformly invoked, but previously unobserved process.